2016
DOI: 10.1073/pnas.1520481113
|View full text |Cite
|
Sign up to set email alerts
|

Emergent ultra–long-range interactions between active particles in hybrid active–inactive systems

Abstract: Particle-particle interactions determine the state of a system. Control over the range of such interactions as well as their magnitude has been an active area of research for decades due to the fundamental challenges it poses in science and technology. Very recently, effective interactions between active particles have gathered much attention as they can lead to out-of-equilibrium cooperative states such as flocking. Inspired by nature, where active living cells coexist with lifeless objects and structures, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…Therefore, we also explore the effect of the spinners' activity on the aggregation dynamics by applying different rotational frequencies, Re = 0.1, 0.72 and 3.58, to spinners embedded in passive matrixes of φ A = 0.8. In agreement with our previous observations for the spinner-spinner interaction in passive environments [22,23], we observe there exists a minimum threshold of loading stress, or spinner activity, for the spinner attractive interaction to be important. Spinners rotating at Re smaller than 0.1 do not aggregate.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, we also explore the effect of the spinners' activity on the aggregation dynamics by applying different rotational frequencies, Re = 0.1, 0.72 and 3.58, to spinners embedded in passive matrixes of φ A = 0.8. In agreement with our previous observations for the spinner-spinner interaction in passive environments [22,23], we observe there exists a minimum threshold of loading stress, or spinner activity, for the spinner attractive interaction to be important. Spinners rotating at Re smaller than 0.1 do not aggregate.…”
Section: Resultssupporting
confidence: 93%
“…5a). The effects of the secondary flow has been attributed to the repulsion between two spheres spinning side-by-side [35,36,46] as well as to an attraction of a single spinner towards a flat wall along the vorticity direction [43]. The stabilisation of the clusters, requires the formation of structures via hydrodynamic interactions at Re ∼ 1.…”
Section: A Inertial Effectsmentioning
confidence: 99%
“…Theg eometry of the suspended objects was expected to play asignificant role in determining the detailed features of such dynamic interactions-which could drive the self-assembly of particles into larger structures without any external interventions.Steimel et al considered atwo-dimensional monolayer of passive colloidal particles and showed that the addition of asmall amount of spinning ferromagnetic colloid facilitated attractive long-range interactions between the active colloid and the tracers,aided by the elasticity of the medium. [140] Theinduced particle interaction depended on the spinning frequency and had am inimum actuation timescale below which no attraction was observed. Ther esults showed that active particles could, in the presence of elastic components,i nteract across very long distances without any chemical modification of the environment.…”
Section: Micronscale Systemsmentioning
confidence: 99%